Microwave-Assisted Preparation of Biodegradable Water Absorbent Polyacrylonitrile/Montmorillonite Clay Nanocomposite - Prafulla K. Sahoo; Trinath Biswal; Ramakanta Samal (Journal of Nanotechnology)
Polyacrylonitrile (PAN)/Montmorillonite (MMT) clay nanocomposite was prepared in a microwave oven using a transition metal Co(III) complex taking ammonium persulfate (APS) as initiator with a motive of converting hydrophobic PAN into hydrophilic nanocomposite material via nanotechnology by the inclusion of MMT to the virgin polymer. UV-visible spectral analysis revealed various interactions between the developed complex with other reaction components. The formation of the PAN/MMT nanocomposites was characterized by FTIR. Furthermore, as evidenced by X-ray diffraction (XRD), transmission electron microscopy (TEM), the composite so obtained was found to have nano-order. XRD and TEM were suggesting that montmorillonite layers were exfoliated during the polymerization process. An increasing in the thermal stability for the developed nanocomposite was recorded by thermogravimetric analysis (TGA). The water absorption and biodegradation properties were carried out for its ecofriendly nature and better commercialization.